Spectroscopic Studies of a New Mixed Ligand Complex of Fe(III) in Aqueous Medium - Aziz, B.K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A spectrophotometric study of Fe(III) mixed ligand complex has been performed involving 1,4 phenylenediamine (A) and anthran i lic acid (B) ligand at 25°C and aconstant ionic strength of µ= 0.05M NaC I04• The optimum pH was found to be pH=4.l. The format ion rat io of the new complex is determined to be 2:1:4 of Fe(III):(A):(B). The molar absorptivity was determined to be :::::: 0.5 x I 04• Stepwise spectrum change of the complex formation is recorded by continuous flow system. Keywords: Mixed ligand complex, Fe(III)